2006
DOI: 10.1242/jcs.03281
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosylphosphorylcholine induces differentiation of human mesenchymal stem cells into smooth-muscle-like cells through a TGF-β-dependent mechanism

Abstract: Mesenchymal stem cells (MSCs) can differentiate into diverse cell types including adipogenic, osteogenic, chondrogenic and myogenic lineages. In the present study, we demonstrated for the first time that sphingosylphosphorylcholine (SPC) induces differentiation of human adipose-tissue-derived mesenchymal stem cells (hATSCs) to smooth-muscle-like cell types. SPC increased the expression levels of several smooth-muscle-specific genes, such as those for α-smooth-muscle actin (α-SMA), h1-calponin and SM22α, as eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
148
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 70 publications
(86 reference statements)
10
148
1
Order By: Relevance
“…Finally, Jeon et al 41 have shown that siRNA-mediated depletion of SRF and/or myocardin abolished SMC differentiation from mesenchymal stem cell because of failure to form SRF/myocardin complex. Therefore we believe Nrf3 mediated upregulation of myocardin may play a crucial role in SMC differentiation from ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Jeon et al 41 have shown that siRNA-mediated depletion of SRF and/or myocardin abolished SMC differentiation from mesenchymal stem cell because of failure to form SRF/myocardin complex. Therefore we believe Nrf3 mediated upregulation of myocardin may play a crucial role in SMC differentiation from ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach has previously been used to induce differentiation of MSCs into smooth muscle-like cells when cultured on 2D tissue culture surfaces. 34,35 Differentiation following TGF-b1 binding results in signaling through the Smad pathway, causing inhibition of cell FIG. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Color images available online at www.liebertpub.com/tec proliferation and induction of contractile proteins in smooth muscle cells. [34][35][36] Incubation of the TIPS microcarriers in the differentiation medium resulted in the induced expression of the three myogenic markers-caldesmon, calponin, and myosin heavy chains. These markers are intermediate to late markers of smooth muscle cell differentiation, unlike a-smooth muscle actin, which is considered to be an early marker of smooth muscle differentiation and, importantly, is not limited only to expression in smooth muscle cells.…”
Section: Figmentioning
confidence: 99%
“…As one important type of adult stem cells, mesenchymal stem cells (MSCs) can be highly expanded in vitro and differentiate into a variety of cell types, such as osteoblasts, adipocytes, myocytes, and so on (1,2). It has been demonstrated that MSCs can differentiate into smooth muscle cells (SMCs) in response to transforming growth factor-b (TGF-b) (3), sphingosylphosphorylcholine (SPC) (4) and directly contact with vascular endothelial cells (5). In vivo, MSCs transplanted into the heart can differentiate into SMCs and contribute to the remodeling of vasculature (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the TGF-b family of cytokines increase the expression levels of SMC-specific genes including a-smooth muscle actin (a-SMA) in a variety of cell types, including human adipose-tissue-derived MSCs (3,4,11,12). TGF-b coordinately upregulates a variety of SMC-specific genes including smooth muscle myosin heavy chain (SMMHC), smooth muscle 22 alpha (SM22a), and a-SMA in cultured SMCs derived from mature blood vessels (11).…”
Section: Introductionmentioning
confidence: 99%